2002
DOI: 10.1021/bc010103m
|View full text |Cite
|
Sign up to set email alerts
|

Polyester Dendritic Systems for Drug Delivery Applications:  In Vitro and In Vivo Evaluation

Abstract: High molecular weight polymers (> 20 000 Da) have been widely used as soluble drug carriers to improve drug targeting and therapeutic efficacy. Dendritic polymers are exceptional candidates for the preparation of near monodisperse drug carriers due to their well-defined structure, multivalency, and flexibility for tailored functionalization. We evaluated various dendritic architectures composed of a polyester dendritic scaffold based on the monomer unit 2,2-bis(hydroxymethyl)propanoic acid for their suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
264
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(268 citation statements)
references
References 37 publications
3
264
1
Order By: Relevance
“…13 For example, a fourth generation polyester dendron attached to a trisphenolic core derived from the monomeric unit bis-MPA has been evaluated for drug delivery applications. 14 Cell proliferation studies have suggested that the dendritic scaffold did not exhibit a significant toxic effect. The attachment of poly(ethylene glycol) to the surface of this type of dendrimer has also been successful for therapeutic applications, 10b,15 and structure− activity relationships have shown that both generation and steric effect are important.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 For example, a fourth generation polyester dendron attached to a trisphenolic core derived from the monomeric unit bis-MPA has been evaluated for drug delivery applications. 14 Cell proliferation studies have suggested that the dendritic scaffold did not exhibit a significant toxic effect. The attachment of poly(ethylene glycol) to the surface of this type of dendrimer has also been successful for therapeutic applications, 10b,15 and structure− activity relationships have shown that both generation and steric effect are important.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In early 2000, this group prepared and evaluated various dendritic architectures composed of a polyester dendritic scaffold based on the monomer unit bis-HMPA for their suitability as drug carriers both in vitro and in vivo [63]. The systems were found to be water soluble and nontoxic.…”
Section: Advances In Polyester Dendrimers For Drug Delivery Applicationsmentioning
confidence: 99%
“…One strategy to overcome these shortcomings is to use polyester dendrimers which have been shown to be non-toxic and biocompatible [19,[56][57][58][59][60]. By attaching a drug to a suitable carrier, it is possible to enhance its aqueous solubility, increase its circulation half-life, target certain tissues, improve drug transit across biological barriers, and slow drug metabolism [61][62][63][64][65][66]. Optimization of these features to maximize drug bioavailability to diseased tissues while minimizing drug exposure to healthy tissues, results in improved therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, the dendritic component of linear dendritic hybrids is a divergently grown dendron, a "wedge-like" dendritic segment. Although numerous dendritic syntheses have been reported (Frechet, Tomalia, 2001), the polyester dendrimers and dendrons based on 2,2-bis(hydroxymethyl)propionic acid (bis-MPA (Ihre et al, 1996;Ihre et al, 2001) are the most promising given their ease of synthesis, exceptional structural purity, and biocompatible nature (Padilla de Jesus et al, 2002;Lundberg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics are particularly important when considering polymers for biomedical applications. One example of the useful modularity of the linear-dendritic hybrid system is that, while the linear PEG provides increased plasma half-life, low toxicity, and overall stability from enzymatic or hydrolytic degradation, the dendrons provide a multiplicity of functional groups to increase the drug payload or targeting groups (Padilla de Jesus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%